PENGARUH MEDIA ULAR TANGGA PINTAR (UTAR) TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPS TEMA KERAGAMAN BUDAYA DI SDN DRINGU TAHUN AJARAN 2022/2023 - Dwi Agustin; Ribut Prastiwi Sriwijayanti; Ryzca Siti Qomariyah (PARAMETER: Jurnal Pendidikan Universitas Negeri Jakarta, 2023)
This study aims to find out empirical answers regarding the effect of using the Smart Ladder Snake (UTAR) media on the learning outcomes of fifth grade students in the social studies subject on the theme of cultural diversity at SDN Dringu in the 2022/2023 academic year. This study used a pre-experimental type of experimental method with the One Group Pretest-Posttest Design. The population in the study were all 21 students of class V, totaling 21 students. The instrument that the researcher used was in the form of multiple choice questions, namely pretest and pretest. The instrument that the researcher used was in the form of multiple choice questions, namely pretest and pretest. Data collection techniques: 1) observation, 2) questionnaire, 3) pretest-posttest results, 4) documentation. The data analysis technique in this research used descriptive data analysis techniques to find out the highest to lowest student scores, and the inferential data analysis technique used to test the hypothesis is the t-test. The results of the study show that: 1) UTAR as a teaching medium is designed according to the development and characteristics of students so that it can motivate fifth grade students in understanding cultural diversity material in social studies subjects. Judging from the scores obtained by students who were initially categorized as low after using teaching media, they were categorized as high, 2) The Smart Snakes and Ladders Media (UTAR) is very influential on student results seen through a questionnaire that has been filled in by students. Abstrak Penelitian ini bertujuan untuk mengetahui jawaban yang empiris mengenai pengaruh penggunaaan media Ular Tangga Pintar (UTAR) terhadap hasil belajar siswa kelas V pada mata pelajaran IPS tema keragaman budaya di SDN Dringu tahun ajaran 2022/2023. Penelitian ini menggunakan metode eksperimen jenis pre-eksperimental dengan bentuk desain One Group Pretest-Posttest Design. Populasi dalam penelitian adalah semua siswa kelas V yang berjumlah 21 siswa. Instrumen yang dilakukan peneliti gunakan adalah dalam bentuk soal pilihan ganda yaitu pretest dan pretest. Teknik pengumpulan data: 1) observasi, 2) angket, 3) hasil pretest-posttest, 4) dokumentasi. Teknik analisis data pada penilitian ini menggunakan tehnik analisis data deskriptif untuk mengetahui hasil tertinggi hingga terendah nilai siswa, dan tehnik analisis data inferensial dengan menggunakan untuk menguji hipotesis adalah Uji-t. Hasil penelitian menunjukkan bahwa: 1) UTAR sebagai media ajar yang dirancang sesuai perkembangan dan karakteristik siwa sehingga dapat memotivasi siswa kelas V dalam memahami materi keragaman budaya pada mata pelajaran IPS dilihat dari nilai yang diperoleh siswa yang mulanya dikatagorikan rendah setelah menggunakan media ajar dikatagorikan tinggi, 2) Media Ular Tangga Pintar (UTAR) sangat berpengaruh terhadap hasil siswa dilihat melalui angket yang telah diisi siswa.